Mengungkap Makna Biaya Haul Nyai Ageng Putri Ayu Kukusan (Studi Etnometodologi) - Syaiful Ukamah; Tumirin Tumirin (Prodi Akuntansi - FEB Universitas Muhammadiyah Gresik, 2020)
This study aims to uncover the meaning of the cost of Haul Nyai Ageng Putri Ayu Kukusan in Gresik Regency. This research was conducted at the Secretariat located on Jl Sunan Prapen II Klangonan, Gresik Regency. The method is qualitative with the Ethnomethodology approach. Data were collected through interviews with three informants and observed the actions of informants on the implementation of the Haul Nyai Ageng Putri Ayu Kukusan in Gresik District. The conclusion of this research is the Klangonan community in Gresik Regency has a perspective of the meaning of costs incurred, namely as Ukhuwah Islamiyah, because Ukhuwah Islamiyah is a form of love, as a form of friendship, as a form of building history, and as a form of gratitude.